(untitled) (Analysis in Theory and Applications, 2018)
In the present article, we deal with the so-called overconvergence phenomenon in C of a slightly modified Post-Widder operator of real variable, that is with the extension of its approximation properties from the real axis in the complex plane. In this sense, error estimates in approximation and a quantitative Voronovskaya-type asymptotic formula are established.